Strategic Knowledge Management System As A Competitive Means For Branding Excellence Of SMEs In Malaysia - Najmaei, Arash (2009)
This study consists of a model illustrating the role of organizational knowledge management system executed at SMEs in order to improve and ameliorate branding behavior.